2011
DOI: 10.1159/000324104
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Management of Spontaneous Retroperitoneal Hemorrhage

Abstract: Wünderlich’s syndrome is a spontaneous nontraumatic massive retroperitoneal hemorrhage. It is usually secondary to a renal neoplasm, with angiomyolipoma being the most frequent followed by renal cell carcinoma. The management of spontaneous retroperitoneal bleeding varies depending on the hemodynamic status of the patient. We present the first report of a transperitoneal laparoscopic nephrectomy in a patient with spontaneous retroperitoneal active bleeding secondary to a right renal mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The first reported case about laparoscopic management of WS was published in 2011 [ 7 ]. In patient with ruptured AML laparoscopic nephrectomy was done in the acute phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first reported case about laparoscopic management of WS was published in 2011 [ 7 ]. In patient with ruptured AML laparoscopic nephrectomy was done in the acute phase.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical time was 250 minutes and blood loss 2000 mL (including hematoma). Peña et al presented four patients with WS treated by laparoscopy [ 7 ]. The cause of the bleeding was AML in two patients and papillary renal cell cancer in two patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the applicability of these technologies during emergencies remains debatable. In 2011, Pena et al [ 13 ] reported the first case of laparoscopic treatment of ruptured angiomyolipoma (AML) during the acute bleeding phase. The transperitoneal approach was employed, with an operation time of 250 min and blood loss of 2000 mL (including hematoma).…”
Section: Introductionmentioning
confidence: 99%
“…To date, LN has been successfully performed for a variety of benign and malignant conditions that were traditionally considered relatively contraindicated. LN for spontaneous nontraumatic retroperitoneal hemorrhage secondary to renal neoplasm 4,5 and late LN for previously documented renal trauma using the transperitoneal approach 6 have been reported.…”
Section: Introductionmentioning
confidence: 99%